2015
DOI: 10.1021/acs.molpharmaceut.5b00705
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding Interactions in Amorphous Indomethacin and Its Amorphous Solid Dispersions with Poly(vinylpyrrolidone) and Poly(vinylpyrrolidone-co-vinyl acetate) Studied Using 13C Solid-State NMR

Abstract: Hydrogen bonding interactions in amorphous indomethacin and amorphous solid dispersions of indomethacin with poly(vinylpyrrolidone), or PVP, and poly(vinylpyrrolidone-co-vinyl acetate), or PVP/VA, were investigated quantitatively using solid-state NMR spectroscopy. Indomethacin that was (13)C isotopically labeled at the carboxylic acid carbon was used to selectively analyze the carbonyl region of the spectrum. Deconvolution of the carboxylic acid carbon peak revealed that 59% of amorphous indomethacin molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
115
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(132 citation statements)
references
References 44 publications
17
115
0
Order By: Relevance
“…This was the case for all SD formulations, as shown in Figure 2a. There was no change in the vinyl acetate C=O carbonyl due to weaker hydrogen bonding potential of the vinyl acetate carbonyl as reported by Yuan et al (2015) as shown in Figure 2b [22]. Any P407 peaks within the pure P407 sample were completely absent in the ATR-FTIR spectra of the SD formulations as shown in Figure 2a and Figure 3.…”
Section: Atr-ftir and Raman Studiessupporting
confidence: 59%
See 2 more Smart Citations
“…This was the case for all SD formulations, as shown in Figure 2a. There was no change in the vinyl acetate C=O carbonyl due to weaker hydrogen bonding potential of the vinyl acetate carbonyl as reported by Yuan et al (2015) as shown in Figure 2b [22]. Any P407 peaks within the pure P407 sample were completely absent in the ATR-FTIR spectra of the SD formulations as shown in Figure 2a and Figure 3.…”
Section: Atr-ftir and Raman Studiessupporting
confidence: 59%
“…The hydrogen-bonded O-H stretch of the acid, shown in Figure 4, is overlaid on the C-H sharp stretches, as literature has reported that the free carboxylic acid O-H stretch as a result of hydrogen bonding can exist as dimers [23]. It is also important to note that in the ATR-FTIR reference spectrum of aINM, the two C=O bands at 1714 cm −1 (free C=O of carboxylic acid) and 1690 cm −1 (acid-acid dimer C=O stretch) shifted to 1707 There was no change in the vinyl acetate C=O carbonyl due to weaker hydrogen bonding potential of the vinyl acetate carbonyl as reported by Yuan et al (2015) as shown in Figure 2b [22]. Any P407 peaks within the pure P407 sample were completely absent in the ATR-FTIR spectra of the SD formulations as shown in Figures 2a and 3.…”
Section: Atr-ftir and Raman Studiessupporting
confidence: 54%
See 1 more Smart Citation
“…Experimentally, 13 C CPMAS solid-state NMR studies have shown that extensive dilution of indomethacin (another carboxylic acidecontaining drug) in PST polymers is necessary to convert HB indomethacin dimers to monomers, with approximately 50% of molecules remaining in dimers at a concentration of only 0.2% indomethacin. 60 In further support of the conclusion that IBP-IBP hydrogen bonding persists even at high dilution in PST, radial distribution functions, g(r), between the centers of mass of IBP and the monomeric units in either PVP or PST were generated at 50 wt% polymer concentrations. The results, shown in Figure 6, indicate that at any given distance between 1.5 and 14 Å, the g(r) value for IBP-PVP is higher than that for IBP-PST.…”
Section: Hydrogen Bonding and Associated Molecular Distributions In Tmentioning
confidence: 72%
“…The possible hydrogen-bonding states in neat Carbopol 907 included a cyclic COOH-to-COOH dimer, COOH-to-carbonyl C¼O, COOH-to-H 2 O, and free unbound COOH. Recently, Yuan et al 35 have assigned different H-bonding states in amorphous indomethacin using 13 C solid-state NMR, aided by comparison to carboxyl chemical shifts in crystalline polymorphs with known H-bonding motifs. They have shown the highest frequency COOH peak in indomethacin to be cyclic H-bonded dimer (179.3 ppm), followed by a COOH chain (176.3 ppm), COOH H-bonded to carbonyl C¼O (172.4 ppm), and free COOH at lowest frequency (170.4 ppm).…”
Section: Solid-state 13 C Nmr To Characterize the Hydrogen Bond Intermentioning
confidence: 99%